Dose-related Effects of Controlled Release Dihydrocodeine on Oro-Cecal Transit and Pupillary Light Reflex - Freye, Enno; Baranowski, Jevgeni; Latasch, Leo (Arzneimittelforschung, 2001)
It is well accepted that long-term administration of opioids results in a dose-related constipation. No data so far have demonstrated conclusively whether such constipation is also seen after intake of a controlled release formulation. It was therefore of interest to evaluate whether increasing doses of a controlled release formulation of dihydrocodeine (DHC, CAS 125-28-0) after oral administration also induces a dose related increase in constipation. Additionally, it was of inter estto study whether such a peripheral opioid related side effect is also seen in another, central receptor mediated effeet, the constriction of the pupil, at clinically relevant doses. Twelve volunteers were given controlled release DHC (60 and 120 mg, respectively) or placebo orally within a randomized, double-blind cross over study. In order to determine the degree of constipation, orocecal transit time was measured using the H2 exhalation test. Additionally, in order to evaluate a centrally mediated effect, the response of the pupil to light was quantified using the pupillary light reflex technique. Both, peripherally and centrally mediated effects were compared to placebo.DHC at both dosages induced a significant (p < 0.01) prolongation of orocecal transit time when compared to placebo. However, prolongation of orocecal transit was not significantly longer when comparing the lower (60 mg) with the higher dose (120 mg). DHC also induced a significant (p < 0.005) depression of the pupillary light reflex from 53.9 mm (control) to 8.3 and 7.4 mm, respectively. Similar to intestinal transit, the pupillary light reflex was not significantly different among the two doses of DHC.Also, both dosages induced a similar amount of side effects. Tiredness and dry mouth were reported in 80 % after both doses while vertigo was reported in 5 % and 1 % complained of headache. None of the volunteers reported nausea or emesis. It is concluded that opioid receptor sites, which are located in the plexus my entericus of the intestinal wall, are responsible for the delay in propulsion. Be cause of the controlled release of a fixed amount of DHC over time there is constant binding of the ligand followed by a constant conformational change of periplierai and central receptor sites. Thus constant release induces no dose related increase in orocecal transit and inhibition of the pupillary light reflex.
Keywords: CAS 125-28-0; Dihydrocodeine, controlled release formulation, by orocecal transit, pupillary light; reflex, volunteers